Spectroscopic properties of natural flavonoids - Brahmachari, Goutam (World Scientific Publishing Company Pte Limited, 2019)
"This book offers physical characteristics and spectral data of 150 selected natural compounds arranged according to their chemical structures in various sub-classes. These include natural source, molecular formula, chemical structure, physical characteristics (melting point, molecular weight, and specific rotation) and detailed spectral data (UV, FT-IR, 1H-NMR, 13C-NMR, 2D-NMR, Mass) along with their assignments for each compound."--